Assessing Expression in the Poetry Reading Skills of Elementary Students - Suma, Mansyur (International Journal of Language Education, 2020)
This study aimed at describing the expression of the fourth-grade students in reading poetry at SDN Bontokamase Gowa. The study was a quantitative descriptive study. The population was the students in all elementary schools in Gowa district. The sample of the study was all students in grade IV at SDN Bontokamase Gowa that consisted of 20 female and 17 male. The data of the study were collected through observation, documentation, and field note. The three instruments were used to see the students’ performance in reading poetry through direct observation, video, literature, and other supported sources. The data were analyzed by using the quantitative descriptive analysis to understand the expression of fourth-grade students in reading poetry. From the direct observation of students' performance in reading poetry, it was found that there are 14 students with a high score, 19 students with medium score and there were 4 students with low score assessed by three assessors. The students with a very good score show very good appreciation. In this case, the very good appreciation or performance is giving appropriate expression in reading title, lines, and rhymes. In contrast, the four students with a low score cannot show good performance or giving flat expression in reading title, lines and rhymes. The average score of students' expression is 3. 13. Thus, it was concluded that the skills to read the poetry of students in terms of expression aspect was in a good category.